Canadian International Petroleum Conference 2000
DOI: 10.2118/2000-063
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Gas Drive in Heavy Oil: Field Prediction and Sensitivity Studies with Low Gas Phase Relative Permeability

Abstract: The favourable behaviour of heavy oil reservoirs under solution-gas drive has intrigued the oil industry for long. Many mechanistic models have been proposed to explain this behaviour. It is believed that the flow in heavy oil reservoir is quite complex and cannot be represented by one theory alone. This paper investigates one of the theories that attribute this behaviour of heavy oil reservoirs to low gas mobility. Simulation is carried out on a commercial black oil simulator to match the production data of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Kumar and Pooladi-Darvish pointed out that at early stages the size of the bubbles is too small and can be neglected; nonetheless, it is at this stage that gas supersaturation is starting, and along with oil production, it eventually reaches bubble nucleation. This phenomenon can be observed in the pressure profiles when the recordings in the pressure gauges start deviating from the pressure in the producing end.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar and Pooladi-Darvish pointed out that at early stages the size of the bubbles is too small and can be neglected; nonetheless, it is at this stage that gas supersaturation is starting, and along with oil production, it eventually reaches bubble nucleation. This phenomenon can be observed in the pressure profiles when the recordings in the pressure gauges start deviating from the pressure in the producing end.…”
Section: Resultsmentioning
confidence: 99%
“…These reservoirs are characterized as having very viscous oils with very low mobility . An anomalous fluid flow behavior has been observed in reservoirs in Venezuela, China, Albania, Oman, and Western Canada, of which have been produced under primary production with a solution gas-driven mechanism. This atypical behavior involves low producing gas–oil ratios (GOR), good pressure maintenance, and prominent primary production recovery when compared with conventional solution gas drive performance. On the other hand, gas injection into heavy oil reservoirs is a common practice as the primary depletion results in low recovery factors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that matching of field (6) and laboratory depletion data (5) required assigning extremely low values of gas relative permeability. The relative permeability functions of these studies, however, were obtained through history matching.…”
Section: Introductionmentioning
confidence: 99%